Prabowo Subianto's Representation in the 2019 Presidential Election and 2024 Presidential Election in Mojokdotco Posts on Instagram: Multimodal Discourse Analysis - Pendri, Apri; Nesti, Meksi Rahma; Wahyudi, M. (Jurnal Hata Poda, 2024)
AbstractThis research is motivated by how Prabowo's figure is represented in the Mojokdotco Instagram account in the context of the 2019 and 2024 presidential elections. Prabowo's representation in this account is of course inseparable from certain aims, objectives and interests. The aim of this research is to compare Prabowo Subianto's personality in Mojokdoco's Instagram posts in the 2019 and 2024 presidential elections using multimodal discourse analysis. Mojokdotco's posts were analyzed using the Kres and Leuween model of multimodal analysis theory. Kres and Leuween's Multimodal Analysis prioritizes analysis on lexical and visual aspects. Lexical aspect analysis will focus on the use of word connotation, overlexicalisation and lexical choices features. Then, visual analysis focuses on the use of participant features, iconography, gaze, composition, setting, distance, salience. The method used in this research is a qualitative method with a descriptive paradigm. This research will focus on revealing the lexical and visual meanings displayed in an infographic about Prabowo. The results of this research are that there is the use of various visual features in Mojokdotco's uploads in the 2019 and 2024 presidential elections about the figure of Prabowo Subianto.Keywords: multimodal discourse analysis; Prabowo; Presidential Elactions.AbstrakPenelitian ini dilatarbelakangi bagaimana sosok Prabowo di representasikan dalam akun Instagram Mojokdotco dalam konteks Pilpres 2019 dan 2024. Representasi Prabowo dalam akun tersebut tentunya tidak terlepas dari maksud, tujuan, dan kepentingan tertentu. Tujuan penelitian ini adalah membandingkan personal Prabowo Subianto dalam unggahan Instagram Mojokdoco pada Pilpres 2019 dan 2024 dengan menggunakan analisis wacana multimodal. Unggahan-unggahan Mojokdotco dianalisis menggunakan teori analisis multimodal model Kres dan Leuween. Analisis Multimodal Kres dan Leuween mengedepankan penganalisisan pada aspek leksikal dan visual. Analisis aspek leksikal akan berfokus pada penggunaan fitur word connotattion, overlexicalisation dan lexical choices. Kemudian, analisis visual berfokus pada penggunaan fitur participant, iconografi, gaze, composition, setting, distance, salience. Metode yang digunakan dalam penelititan ini adalah metode kualitatif dengan pradigma deskriptif. Penelitian ini akan berfokus pada pengungkapan makna leksikal dan visual yang ditampilkan dalam satu bentuk infografis tentang Prabowo. Hasil dalam penelitian ini adalah terdapat penggunaan berbagai fitur visual dalam unggahan Mojokdotco pada Pilpres 2019 dan 2024 tentang sosok Prabowo Subianto.Kata Kunci: analisis wacana multimodal; Prabowo; Pilpres